Durabilidade de concretos à base de cimento álcali ativado: aspectos relacionados à carbonatação - Cadore, Douglas Éverton (2018)
The iron manufacture generates a discard product, the blast furnace slag, and one of the main exposure characteristics is a CaO / SiO2 ratio. The following relationship is commonly found in the literature: acid slags (CaO / SiO2 <1) and basic slags (CaO / SiO2 > 1). These alkaline activated slags produce a binder (activated alkali cement - CAT) of low environmental impact, whose main product of hydration is a C-A-S-H gel. Researches have presented satisfactory results of this material in terms of mechanical resistance, however, durability still need investigations. So, the objective of this study is to analyze CAT durability parameters in concrete based on acid slag, specifically resistance to carbonation. For this, an experimental program was developed, where accelerated carbonation tests were performed on samples of CAT concrete and Portland cement (PC) concrete. The elaborated concretes were inserted in a carbonation chamber with controlled temperature, humidity and CO2, for a 4, 8, 12 and 16 weeks. Complementary tests of resistance, water absorption and shrinkage were also performed in order to analyze their results together with the carbonation depth result. In order to basis for the analysis of the durability results, microstructural investigations were elaborated. CAT concrete presented carbonation depth higher than CP concrete, having as carbonation coefficients 3.67 and 2.32 mm/week0,5, respectively. It should be noted that the evolution of carbonation was more significant in the first test period (4 weeks), which may be due to the precipitation of CaCO3 in the pores of the compound. The carbonation result can be justified by the more intense shrinkage in CAT concrete, since the hydration products are less crystalline than in the CP, and the differentiated pore structure of that compound may also have influenced the result. It was also found more severe loss of resistance in CAT after the carbonation period and this finding is based on the compounds attacked by carbonation, in the CAT this compounds is the CSH, since it does not have the hydration product Ca(OH)2. Thus, the durability of CAT against carbonation should be further investigated, with the objective of conditioning this material to better resistance results to this attack.